Persistent Expression of Serotonin Receptor 5b Alters Breathing Behavior in Male MeCP2 Knockout Mice - Vogelgesang, Steffen; Niebert, Marcus; Bischoff, Anne M.; Hülsmann, Swen; Manzke, Till (Frontiers in Molecular Neuroscience, 2018)
Mutations in the transcription factor methyl-CpG-binding protein 2 (MeCP2) cause a delayed neurodevelopmental disorder known as Rett syndrome (RTT). Among many other neurological problems RTT patients show irregular breathing with recurrent apneas or breath-holdings. Mecp2–deficient mice, which recapitulate this breathing phenotype, show a dysregulated expression of G-protein-coupled serotonin receptor 5-ht5b (Htr5b) in the brainstem. Since 5-ht5b receptors couple to Gi proteins, we measured cAMP levels in brainstem tissue, and found that, unlike in WT and Mecp2-/y;Htr5b-/- mice, cAMP levels in Mecp2-/y mice were decreased. Using unrestrained whole-body plethysmography, we investigated, whether the persistence of 5-ht5b expression in older Mecp2-/y mice is contributing to the respiratory phenotype. The breathing of MeCP2-deficient male mice at postnatal day 40 was characterized by a slow breathing rate and the occurrence of prolonged respiratory pauses. In contrast, we found that both breathing rate and number of pauses in MeCP2-deficient mice, which also lacked the 5-ht5b receptor (Mecp2-/y;Htr5b-/-) was indistinguishable from wild type (WT) and Htr5b-/- mice. Taken together, our data points towards a role of 5-ht5b receptors within the breathing complex phenotype of MeCP2-deficient mice.